Segmentation of objects in images using physical principles - Patrícia C. T. Gonçalves (2008)
The final goal of this work is to automatically extract the contour of an object represented in an image after manually defining an initial contour for it. This rough initial contour will then evolve until it equals the border of the desired object. The contour is modelled by a physical formulation, using the Finite Element Method, and its evolution to the desired final contour of the object to segment is governed by several forces: internal forces, defined by intrinsic physical characteristics selected for the model; and external forces, defined in function of image features that best represent the desired object. To physically model the considered contour we adopt Sclaroffs isoparametric finite element, and to obtain the evolution of the model towards the object border we use Nastars methodology that consists in solving the dynamic equilibrium equation.